Actualización en el manejo, factores de riesgo y tratamiento del embarazo ectópico. - Gavilanes Orozco, Verónica Mercedes (2025)
Ectopic pregnancy is a gynecological condition of considerable clinical relevance due to the potential risk it poses to the patient’s life if not identified and managed in a timely manner. Its appropriate management requires the implementation of modern diagnostic and therapeutic strategies capable of addressing the heterogeneity of its clinical manifestations. The aim of this research is to propose evidence-based recommendations to optimize the comprehensive management of this condition. To achieve this objective, a systematic review was carried out in accordance with the standards established by the PRISMA methodology, using PubMed, ScienceDirect, SciELO, and Dialnet as primary information sources. The Joanna Briggs Institute (JBI) checklist was applied for the critical appraisal of the selected studies. The results indicate that the combined use of serum β-hCG measurement and transvaginal ultrasound yields a sensitivity ranging from 87% to 99% and a specificity between 94% and 99%. The most reliable diagnostic indicator is the absence of an intrauterine gestational sac when β-hCG levels surpass the established discriminatory value. With regard to treatment, methotrexate demonstrated success rates ranging from 40% to 77.5%, proving to be more effective in hemodynamically stable patients with low serum β-hCG levels, gestational masses smaller than 35 mm, and in the absence of embryonic cardiac activity. Surgical intervention remains a critical option in complicated cases, offering high success rates and low reported mortality. In this context, early detection relies on the accurate interpretation of biochemical markers in conjunction with ultrasound findings. Treatment decisions should be individualized based on both clinical presentation and laboratory parameters. Consequently, there is a need for standardized protocols that incorporate accessible diagnostic tools and well-defined criteria for selecting the safest and most effective therapeutic approach for each clinical scenario.